PENGARUH PEMBERIAN AROMATERAPI SEREH TERHADAP KUALITAS TIDUR PADA LANSIA DENGAN HIPERTENSI - Salma Safinatunnajah; Imam Subekti; Nurul Pujiastuti (Jurnal Keperawatan Terapan, 2024)
Poor sleep quality reduces antibodies and increases feelings of weakness and fatigue, the hormone cortisol and sympathetic nervous system will change when a person's sleep quality is poor which can cause blood pressure to increase (1). Aromatherapy is one of the nonpharmacological therapies that can be performed where aromatherapy does not cause dependence. The aim of this study is to look at the effect of lemongrass aromatherapy on sleep quality in the elderly who suffer from hypertension. This research is pre-experimental research, a design used that is pretest-postest for one group. This study uses a quota sampling method with a sample number of 10 elderly people based on inclusion and exclusion criteria. The PSQI questionnaire is used as an instrument of data collection. The intervention is in the form of lemongrass aromatherapy through a reed diffuser. Because the data is not normally distributed, the Wilcoxon test is used. The results of the study were obtained p-value of 0.01 which showed that there were differences in sleep quality before and after obtaining lemongrass aromatherapy, meaning that there was an influence on the administration of lemongrass aromatherapy to sleep quality in hypertensive elderly people.